Rodzina w polityce społecznej II Rzeczypospolitej. Analiza wybranych kierunków działań - Majchrzyk-Mikuła, Joanna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
A groundbreaking moment for the newly born state and its social institutions was the introduction, after regaining independence in 1918, of the social security system and public health care system. The issue of social welfare was legally solved by the introduction of the bill from August 16, 1923. The protection of maternity, infants, children and young persons became one of the most important issues of social welfare activity. Among the numerous supporting activities, obviously the most meaningful Rodzina w polityce społecznej II Rzeczypospolitej role was to provide basic living conditions for the poorest people. Previous philanthropic activity was insufficient and ineffective and it had to be replaced with planned, rational and organized social work. Social legislation, created with great effort, was aimed at creating the rights for each man to a decent human existence. At the same time, this legislation shaped and helped to create the state which would be responsible for its citizens.
Keywords: family; child; health care; the Second Polish Republic